PENGARUH INTENSITAS PENGGUNAAN MEDIA SOSIAL TERHADAP PERILAKU IMITASI PESERTA DIDIK DI SMA N 5 PADANG - Helfines, Monica (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2025)
Penelitian ini dilatar belakangi oleh adanya peserta didik yang kurang perhatian saat belajar, adanya peserta didik yang sulit terfokus saat belajar, adanya peserta didik yang bermain-main saat belajar, dan adanya peserta didik yang meniru tingkah laku di media sosial dengan circle atau berkelompok. Tujuan penelitian ini adalah mendeskripsikan: 1) Intensitas media sosial di SMAN5 Padang, 2) Perilaku imitasi peserta didik di SMAN 5 Padang, 3) Untuk menguji pengaruh intensitas penggunaan media sosial terhadap perilaku imitasi peserta didik di SMAN 5 Padang. Penelitian ini dilakukan dengan menggunakan metode deskriptif kuantitatif dengan analisis korelasi. Populasi penelitian ini adalah peserta didik kelas XI Fase F SMA N 5 Padang tahun ajaran 2023/2024 yang berjumlah 358 orang peserta didik. Teknik pengambilan sampel ini dilakukan dengan Teknik Purposive sampling yaitu sebanyak 72 orang peserta didik yang menjadi sampel penelitian. Teknik analisis data yang digunakan adalah presentase dan uji korelasi.Hasil penelitian ini menujukan bahwasanya pengaruh intensitas penggunaan media sosial terhadap perilaku imitasi peserta didik di kelas XI Fase F SMA N 5 Padang dapat di ambil kesimpulan sebagai berikut: 1) Pengaruh intensitas penggunaan media sosial terhadap perilaku imitasi peserta didik di kelas XI Fase F SMA N 5 Padang berada kategori tinggi, 2) Perilaku imitasi peserta didik di kelas XI Fase F SMA N 5 Padang berada pada kategori tinggi, 3) Pengaruh penggunaan media sosial terhadap imitasi peserta didik di kelas XI Fase F SMA N 5 Padang berada pada kategori tinggi adalah sebesar -0,077 dengan koefisien pengaruh yang tinggi. Berdasarkan hasil penelitian ini direkomendasikan kepada guru BK agar peserta didik mampu meningkatkan pengaruh intensitas penggunaan media sosial peserta didik supaya perilaku imitasi peserta didik semakin berjalan sesuai arahannya. This research is motivated by the existence of students who lack attention while studying, the existence of students who have difficulty focusing while studying, the existence of students who play around while studying, and the existence of students who imitate behavior on social media with circles or groups. The purpose of this study is to describe: 1) The intensity of social media at SMAN5 Padang, 2) The imitation behavior of students at SMAN 5 Padang, 3) To test the effect of the intensity of social media use on the imitation behavior of students at SMAN 5 Padang. This research was conducted using a quantitative descriptive method with correlation analysis. The population of this study was class XI Phase F students of SMA N 5 Padang in the 2023/2024 academic year totaling 358 students. The sampling technique was carried out using the Purposive sampling technique, namely 72 students who were the research samples. The data analysis techniques used were percentage and correlation test. The results of this study indicate that the influence of the intensity of social media use on the imitation behavior of students in class XI Phase F of SMA N 5 Padang can be concluded as follows: 1) The influence of the intensity of social media use on the imitation behavior of students in class XI Phase F of SMA N 5 Padang is in the high category, 2) The imitation behavior of students in class XI Phase F of SMA N 5 Padang is in the high category, 3) The influence of social media use on the imitation of students in class XI Phase F of SMA N 5 Padang is in the high category is -0.077 with a high influence coefficient. Based on the results of this study, it is recommended to BK teachers so that students are able to increase the influence of the intensity of students' use of social media so that students' imitation behavior continues to run according to their direction.This research is motivated by the existence of students who lack attention while studying, the existence of students who have difficulty focusing while studying, the existence of students who play around while studying, and the existence of students who imitate behavior on social media with circles or groups. The purpose of this study is to describe: 1) The intensity of social media at SMAN5 Padang, 2) The imitation behavior of students at SMAN 5 Padang, 3) To test the effect of the intensity of social media use on the imitation behavior of students at SMAN 5 Padang. This research was conducted using a quantitative descriptive method with correlation analysis. The population of this study was class XI Phase F students of SMA N 5 Padang in the 2023/2024 academic year totaling 358 students. The sampling technique was carried out using the Purposive sampling technique, namely 72 students who were the research samples. The data analysis techniques used were percentage and correlation test. The results of this study indicate that the influence of the intensity of social media use on the imitation behavior of students in class XI Phase F of SMA N 5 Padang can be concluded as follows: 1) The influence of the intensity of social media use on the imitation behavior of students in class XI Phase F of SMA N 5 Padang is in the high category, 2) The imitation behavior of students in class XI Phase F of SMA N 5 Padang is in the high category, 3) The influence of social media use on the imitation of students in class XI Phase F of SMA N 5 Padang is in the high category is -0.077 with a high influence coefficient. Based on the results of this study, it is recommended to BK teachers so that students are able to increase the influence of the intensity of students' use of social media so that students' imitation behavior continues to run according to their direction.